Low viral load of Merkel cell polyomavirus in Iranian patients with head and neck squamous cell carcinoma: Is it clinically important?. Issue 2 (20th October 2017) - Mohebbi, Elham; Noormohamadi, Zahra; Sadeghi‐Rad, Habib; Sadeghi, Farzin; Yahyapour, Yousef; Vaziri, Farzam; Rahimi, Ayoub; Rahimi Jamnani, Fatemeh; Mehrabi, Saman; Siadat, Seyed D.; Noori‐Daloii, Mohammad R.; Fateh, Abolfazl
Abstract : Recent studies show that the human Merkel cell polyomavirus (MCPyV) may be involved in causing cancer. The objective of this study was to assess the impact of MCPyV on the development of head and neck squamous cell carcinoma (HNSCC). In total, 50 paraffin‐embedded HNSCC biopsy samples and 50 adjacent non‐cancerous samples were evaluated for the presence of MCPyV DNA and RNA. Among patients, the five most frequent histopathologic sites were the tongue (22.0%), lip (16.0%), submandibular (14.0%), cheek (14.0%), and throat (14.0%). MCPyV DNA was positive in eight (16.0%) samples. The median MCPyV LT ‐Ag copy number in the eight positive samples and in one non‐cancerous sample was 4.8 × 10 −3 and 2.6 × 10 −5  copies/cell, respectively. Quantification of MCPyV LT ‐Ag revealed increased expression in stage III (5.6 × 10 −3  copies/cell) than in the other stages. The MCPyV DNA load in different stages of HNSCC was also statistically significant ( P  = 0.027). The viral load was low, suggesting that only a fraction of cancerous cells is infected. This result provides evidence confirming the presence of MCPyV in a subset of Iranian patients with HNSCCs, but further studies needed to confirm our findings.